2015
DOI: 10.1016/j.ijmedinf.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of inactive health information seekers

Abstract: Purpose This study aims to identify people who do not actively seek out health information and the demographic characteristics of Inactive Seekers. The possible determinants of inactive seeking behaviors is also explored. Design and Measurements A total of 14,420 survey respondents were drawn from the 2009 Annenberg National Health Communication Survey (ANHCS) data. K-means clustering was used to discriminate Inactive Seekers from Active Seekers. The inactive information seeker group was formed based on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 88 publications
3
29
2
Order By: Relevance
“…However, the majority of the respondents report that they sought health information through family members first. This result is not consistent with other studies reporting that healthcare providers are initially or most frequently sought out as a health information source [1,25,36] and is tied to our previous discussion about college students' transitioning phase of information dependency.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the majority of the respondents report that they sought health information through family members first. This result is not consistent with other studies reporting that healthcare providers are initially or most frequently sought out as a health information source [1,25,36] and is tied to our previous discussion about college students' transitioning phase of information dependency.…”
Section: Discussioncontrasting
confidence: 99%
“…Compared to other studies, this sample prefers depending more on family for health information sources than healthcare professionals [1,33]. Although this is not a direct comparison, the average number of clinic visits in this sample was 4.32 times in the past year, implying a relatively healthy population compared to the national average of 12.9 visits in 2001 and 11.6 visits in 2010 among people aged 18 to 64 who reported fair or poor health [40].…”
Section: Research Question 1: Sample Characteristicsmentioning
confidence: 81%
“…The literature reports that men seek health information less often than women . Moreover, men are more likely to engage in passive information‐gathering, whereas women are more likely to be active information‐seekers …”
Section: Introductionmentioning
confidence: 99%
“…Demographic profiles of inactive seekers by Ramanadhan and Viswanath suggest that those who do not seek out information ‘came from the lowest income and education groups and scored lower on attention to, and trust in, media health information’ . More recently, Kim found that inactive health information seekers could be profiled based on certain demographic characteristics as well, but that study did not address vaccinations among health care workers. As such, there is little research to indicate a linkage between inactive information‐seeking and vaccination uptake among health care workers.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that information subjective norms – perceived social pressure to remain informed about vaccination – were a strong predictor of information‐seeking while neither source credibility nor information usefulness independently increased explained variance. From an evidence‐based information service point of view, Mortensen et al reported positive aspects of information service given to health care workers to improve vaccination uptake . Clearly, a research gap exists to identify a group of health care workers who are less active in seeking influenza information while others are more active in pursuing this critical information.…”
Section: Introductionmentioning
confidence: 99%